2022
DOI: 10.1111/jopr.13576
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intraoral Scanners in the Shade Matching Process: A Systematic Review

Abstract: Purpose The variation in findings with regards to the accuracy and precision of intraoral scanners for shade selection are no doubt confusing for clinicians who may find it difficult to make evidence‐based decisions. The aim of this systematic review is to provide a comprehensive and in‐depth assessment of available studies to determine the viability of using intraoral scanners for the purpose of shade matching. The PICO‐guided research question is as follows: when shade matching, are intraoral scanners as val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…When intraoral scanners are used to obtain digital impressions or for shade matching, several factors can influence the accuracy of outcomes. These include technology and system selection, ambient lighting conditions, operator experience, wetness, and existing restorations 61,62 . The effects of these factors on the ability of intraoral scanners to diagnose caries have not been extensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…When intraoral scanners are used to obtain digital impressions or for shade matching, several factors can influence the accuracy of outcomes. These include technology and system selection, ambient lighting conditions, operator experience, wetness, and existing restorations 61,62 . The effects of these factors on the ability of intraoral scanners to diagnose caries have not been extensively studied.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results from different studies are conflicting, recent systematic reviews on intraoral scanners' color capturing accuracy concluded that intraoral scanners showed high precision, but inconclusive trueness in shade selection. 26,27 Application of multicolor 3D-printing using material jetting technology is relatively new in dentistry. It was reported that color reproduction accuracy of multicolor material jetting printers met the criterion of color quality in everyday contexts with various illumination.…”
Section: Discussionmentioning
confidence: 99%
“…The color capturing accuracy of the intraoral scanners has been studied extensively. Although the results from different studies are conflicting, recent systematic reviews on intraoral scanners' color capturing accuracy concluded that intraoral scanners showed high precision, but inconclusive trueness in shade selection 26,27 . Application of multicolor 3D‐printing using material jetting technology is relatively new in dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…The use of commercial shade guides usually leads to unreliable and inconsistent results 1–3 . To overcome this problem, some authors have recommended the use of two or more shade guides 4–16 . Additionally, as the prepared tooth shade influences the final shade of ceramic restorations (Figures 1 and 2), in an attempt to mimic the prepared tooth shade, dental manufacturers introduced to the market a natural color die material with a special dentin shade guide 17–21 .…”
Section: Introductionmentioning
confidence: 99%
“…problem, some authors have recommended the use of two or more shade guides. [4][5][6][7][8][9][10][11][12][13][14][15][16] Additionally, as the prepared tooth shade influences the final shade of ceramic restorations (Figures 1 and 2), in an attempt to mimic the prepared tooth shade, dental manufacturers introduced to the market a natural color die material with a special dentin shade guide. [17][18][19][20][21] Fabricating a custom-made shade guide by using different porcelain powder combinations might be helpful.…”
mentioning
confidence: 99%